Cooling panel wall system with difference types of cooling mediums - Salleh, Norhafizah; Mohamad Hashim, Eny Nor Syahira; Abd Majid, Masni; Abdul Hamid, Noor Azlina; Ismail, Noorli; Ali, Noorwirdawati; Abdullah, Siti Radziah; Jamellodin, Zalipah; Adnan, Suraya Hani (Penerbit UTHM, 2020)
Global warming has caused worldwide average surface temperature to rise about 0.74oC during the past 100 years, which is partly aggravated by air-conditioning that releases chlorofluorocarbons (CFCs) and forming a vicious cycle. This paper proposes a cooling house system that can promote thermal comfort in buildings without air-conditioning. The cooling panel wall forms a part of an Integrated Building System (IBS), and is essentially made of tubes filled with either water or glycerin as the coolant. Target strength for the panel wall was designed based on the Malaysian Standard (MS) while the building ventilation system followed the American Society of Heating, Refrigerating, and Air Conditioning Engineers (ASHRAE) standard. The results are reported based on indoor and outdoor temperature difference together with relative humidity to identify the best performing house model and also coolant. The outcome of this research is expected to add value to heritage house design concepts with a better promotion of air flow and circulation in the building, without over-usage of natural resources and higher building cost to achieve the same objective.